Problem Based Learning Model Analysis in Improving Student's Critical Thinking Ability - Hestiningtyas, Widya; Rizal, Yoh; Rahmawati, Fanni (Universitas Negeri Semarang, 2021)
This reseach aimed to determine the level of critical thinking skills of Economic Education students at Universitas Lampung in the 2021/2022 academic year through a problem based learning model. The ability to think critically is one indicator of intelligence that must be possessed by every individual in facing the era of society 5.0, in an effort to respond to various challenges in the midst of social life. The population in this study were 256 students with a sample size of 144 students, which was obtained by using the Isaac-Michael formula. Methods of data collection used questionnaires, documentation, and interviews. Based on the results of the study, it was found that there was an effect of applying the problem based learning model on increasing students' critical thinking skills, which was 66.5% and the rest was influenced by other factors.